Using a dialogue journal to develop writing skills - Zulfadli A. Aziz; Nina Magdalena (Universitas Syiah Kuala, 2016)
This study investigates a number of scholars’ opinions regarding the use of dialogue journals for improving the writing skills of young learners. Their views were compiled based on their research findings concerning the use of dialogue journals. This study aims to describe the implementation of dialogue journals in developing the writing skills of young learners. Since this study was conducted in the form of library research, various written resources such as relevant journal articles, textbooks and online documents, as well as reports from previous related research were analyzed to meet the aims of this study. The study mainly used 4 sources of research namely Remiasova (2009), Datzman (2011), Valigurova (2010), Haynes-Mays, Peltier-Glaze, and Broussard (2011). The results show that the use of dialogue journals has improved the writing skills of young learners especially in terms of vocabulary and grammar.